(untitled) (Research, Society and Development, 2021)
Nursing is a great pillar acting in women’s health care, having a fundamental contribution in health education and in carrying out nursing consultations for the prevention and management of cervical cancer. Given this, this study aimed to analyze the actions of nursing care in the prevention and management of cervical cancer, based on a literature review. In carrying out the research, an integrative literature review was used, on the proposed topic, with a qualitative and exploratory approach. Scientific studies were searched in the main databases used around ​​health science (LILACS, Medline, SciElo and PubMed) and the selection of works started with a previous reading of the abstract, to verify the association of the work with the proposed theme. After an extensive literature search, 16 articles that best met the proposed objective were selected. The critical analysis of the information collected from the sampled works made it possible to identify the main meanings in relation to the challenges faced by nursing in the diagnosis of cervical cancer; the role of nursing in the prevention of cervical cancer; and nursing strategies as an effective action to prevent cervical cancer. The role of nurses in health promotion and disease prevention behaviors is very important, as they have an impact on patients’ health promotion activities.